Pre-LGM loess deposits in caves of Polish Jura – occurrence and stratigraphic importance - Krajcarz, Maciej T. (Acta Geologica Polonica, 2023)
Loess is an important component of cave deposits. Loess and loess-like strata in caves and rock shelters may serve as stratigraphic correlative units and paleoclimate indicators. For the Polish Jura (southern Poland), one of the key regions of cave deposits studies in Europe, the published information concerning the stratigraphic importance of loess is limited to the sequences from around the Last Glacial Maximum (LGM). In this paper, a review of the archival data about loess deposits situated below the LGM strata in caves and rock shelters of the Polish Jura is presented. The paper discusses the occurrence, lithology, stratigraphy, chronology and paleoecology of the pre-LGM cave loess. The most important sites of the pre-LGM cave loess in the region include: Biśnik Cave, Nietoperzowa Cave, Mamutowa Cave, and Ciemna Cave (only the outer zones). The loess strata in these sites correlate with cold Marine Isotope Stages (MIS): mid-3, 4, 5b–d, 6, and possibly 10. They represent all the main facies of cave loess: typical eolian loess, colluviated loess-like deposits, loess with bedrock debris, and loams of complex grain-size composition but with the predominance of a loess component. Stratigraphic correlations with loess-paleosol sequences are proposed.
Keywords: Cave deposits; loess; Stratigraphy; Pleistocene; Kraków-Częstochowa Upland; Poland